Free speech and censorship : examining the facts - Pohlman, H. L., 1952- (Contemporary debates., 2019)
This book provides an overview of laws and norms regarding free speech and censorship in the United States, with a focus on free speech rights and restrictions for individuals, politicians, corporations, and news organizations. It examines beliefs, claims, and myths about free speech and censorship issues, including landmark court decisions and evolving cultural values that have shaped our understanding of the First Amendment and the liberties it enshrines and protects.